Corporate structure and prevention: The three lines model applied to Latin American companies - Lizarzaburu, Edmundo (2024)
The economic environment in which enterprises operate is increasingly harsh and complex, making business more complex, volatile and uncertain. This context requires a change in the management model based on the three fundamental pillars of governance, risk management and regulatory compliance. In this sense, the presentation of the three-line model is considered particularly useful, as it has become one of the most recognized management tools internationally due to its flexibility and adaptability. Therefore, the purpose of this study is to examine the current literature on this management model and then analyze its applicability in business practice through a case study. In particular, the analysis of four companies in the Ibero-American energy sector (Petrobras, Codelco, Ecopetrol, and Iberdrola) reveals that, although the adaptation of the model is generally comprehensive and universal in all aspects, its flexibility is very Large allows adaptation to any organization’s needs and structure. Finally, the study draws some conclusions weighing the theoretical development of the three-line model and its applicability and usefulness to managers as well as researchers and legislators who want to strengthen national business structures.